Structural and functional characterisation and regulatory mechanisms of SWI/SNF and RSC chromatin remodelling complexes in fungi - Lirong Zhu; Qianqian Liu; Chao Zhao; Meichen Zhu; Xuewei Yang; Jinkui Yang (Mycology)
Chromatin remodellers utilise energy generated from ATP hydrolysis to remodel nucleosomes and modulate histones, which are crucial for eukaryotic gene expression and chromatin architecture. The SWI/SNF (switching defective/sucrose non-fermenting) class of ATP-dependent chromatin modifiers in eukaryotes includes two complexes, SWI/SNF and RSC (remodeling the structure of chromatin). In the past 10 years, SWI/SNF and RSC chromatin remodellers have been a focus of research in various organisms, including animals, plants and fungi. In fungi, these two complexes have multiple functions, including roles in regulating hyphal differentiation, sporulation, stress responses, and pathogenicity. In addition to describing conserved structural properties and mechanisms of action, we highlight evidence for sequence and functional divergence in fungal evolution. This review provides a basis for further comparative analyses of the roles and regulatory mechanisms of the SWI/SNF and RSC complexes in taxonomically diverse fungi, laying a good foundation for potential applications in controlling pathogenic fungi.